2001
DOI: 10.1263/jbb.91.233
|View full text |Cite
|
Sign up to set email alerts
|

On the Adsorption of Proteins on Solid Surfaces, a Common but Very Complicated Phenomenon.

Abstract: Adsorption of proteins on solid surfaces and their interaction are major concerns in a number of fields such as biology, medicine, biotechnology and food processing, and play an important role from various points of view. Based on practical viewpoints, information on the conformation of the adsorbed protein as well as adsorption characteristics is essential for a system's performance. Although there are still many problems to be solved, extensive studies in recent years, owing to the development in instrumenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
611
1
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 468 publications
(644 citation statements)
references
References 83 publications
28
611
1
4
Order By: Relevance
“…Some aspects remain, however, to be investigated, namely the activity of the enzyme when released from the matrices used in this work (ongoing studies). Although protein immobilisation, either by entrapment or adsorption, often results in conformational alterations that may render the protein inactive, several authors have reported improved enzyme activity and/or stability in immobilised preparations when compared to their free forms [40].…”
Section: Discussionmentioning
confidence: 99%
“…Some aspects remain, however, to be investigated, namely the activity of the enzyme when released from the matrices used in this work (ongoing studies). Although protein immobilisation, either by entrapment or adsorption, often results in conformational alterations that may render the protein inactive, several authors have reported improved enzyme activity and/or stability in immobilised preparations when compared to their free forms [40].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is of crucial importance for many biological and biomedical applications to know if the protein structure will be conserved upon adsorption. 260,261 The conventional answer is negative: adsorption, in particular on silica, changes the folding pattern of the protein chain, in other words it causes denaturation.…”
Section: From Oligopeptides To Proteins: Adsorption Secondary Structmentioning
confidence: 99%
“…In addition, HSA-coated chrysotile nanocrystals have been investigated by FTIR spectroscopy as a function of the protein concentration which induces a different degree of surface coverage. Surface coating extent (G) represents the amount of protein adsorbed (mg m K2 ) at constant temperature on a given substrate and strongly depends on the surface features: a hydrophilic substrate, like chrysotile, may adsorb a much greater protein amount than a hydrophobic one (Nakanishi et al 2001). It is important to take into account that at pH 7.4, HSA (isoelectric point 4.6) and chrysotile (isoelectric point 8-12, according to the different amount of magnesia) are predominantly negatively and positively charged, respectively; thus electrostatic forces play here an important role.…”
Section: Ftir Analysis Of Hsa-coated Chrysotile Nanocrystalsmentioning
confidence: 99%